Graphene as an electrochemical transfer layer. (January 2019) - Sharifi, Tiva; Xie, Yu; Zhang, Xiang; Barzegar, Hamid Reza; Lei, Jincheng; Coulter, Gabriel; Sun, Shiyun; Tiwary, Chandrasekhar; Zettl, Alex; Yakobson, Boris; Ajayan, Pulickel M.
Abstract: The capability of graphene to adopt a property from an adjacent material is investigated by measuring the electrochemical performance of a monolayer graphene placed on top of thin cobalt oxide (Co3 O4 ) nanosheets. In this assembly, monolayer graphene works as an interfacial layer which inhibits the direct contact of the actual electroactive material and electrolyte during electrochemical reaction. The results show that while graphene is electrochemically inert, it behaves as an active material to catalyze oxygen evolution reaction (OER) once placed on top of Co3 O4 nanosheets. The graphene-covered Co3 O4 model system shows electrochemical performance similar to Co3 O4 indicating complete transference of the electrochemical property of the metal oxide to the graphene. Based on density functional theory (DFT) calculations, charge transfer from graphene to Co3 O4 is the key factor for turning the electrochemically inactive graphene to an apparent active material. Graphical abstract: Image 1